Foreign direct investment in different sectors of indian economy - Deepti (New Delhi, 2011)
This book provides a sweeping, up-to-date, and boldly critical account of thefinancial crises that rocked East Asia and other parts of the world beginningwith the collapse of the Thai baht in 1997. Retracing the story of Asia's CrisisFive - Indonesia, Malaysia, South Korea, the Philippines, and Thailand - theauthor argues that the region's imprudently fast-paced opening to the free flowof capital was pushed by determined advocates, official and private, in theglobal economy's U.S.-led developed center. Turmoil ensued in these peripheraleconomies, the Russian ruble faltered, and Brazil was eventually hit. Theinequitable center-periphery relationship also extended to the policy measuresthat the crisis-swept economies implemented under International Monetary Fundbailouts, which intensified the downturns induced by the panic-driven outflowsof short-term capital. Financial Crisis, Contagion, And Containmentexamines crisis origin and resolution in a comparative perspective by combingempirical evidence from the most robust economies to the least. Engaging and nontechnical yet deeply insightful, this book appears at atime when the continuing turmoil in Argentina has revived policy debates foravoiding and addressing financial crises in emerging market economies.
Keywords: Economic reforms-India